If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 8z = 2 + 2y Solving 3x + 8z = 2 + 2y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8z' to each side of the equation. 3x + 8z + -8z = 2 + 2y + -8z Combine like terms: 8z + -8z = 0 3x + 0 = 2 + 2y + -8z 3x = 2 + 2y + -8z Divide each side by '3'. x = 0.6666666667 + 0.6666666667y + -2.666666667z Simplifying x = 0.6666666667 + 0.6666666667y + -2.666666667z
| 4x-7=65 | | 10x+5+4x-7=65 | | (4x-7)(2x-1)=0 | | 3x-2+2x+6+4x-4=180 | | 12d+4=7-d | | 3x-2+2x+6=180 | | -13+2x=x+13 | | 9x+6+10x-1+10x+7=180 | | 10x-1+10x+7=180 | | 1/4=8 | | log(2)x=2 | | -81+9x=179-11x | | -4+(-10)-(-3)-12= | | -44-4x=-12x+52 | | 7-3=-1 | | 21x+50-16x=10 | | 10x+5y+2z+k=100 | | -3/4*-4/9 | | -3/4*-4/8 | | 7x-45=5x-5 | | 160/X=16 | | -14+5= | | K=ka+9ab | | -4x-18=6-6x | | (6x+4)=52 | | (6x+4)=53 | | 1/3•93 | | -8x-14=-10x+22 | | 3m(3m+2)+5=0 | | 3=p*3+q | | 3x+26=x+58 | | 10+11n=10 |